ANALISIS PENDAPATAN AGROINDUSTRI TAHU SUMEDANG “STUDI KASUS AGROINDUSTRI TAHU SUMEDANG BAPAK OSMANDRI” DI DESA TANAH MERAH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Elly Willy Sidabutar; Ermi Tety; Suardi Tarumun (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
The research is aimed to determine (1) the production and marketing process ofsumedang raw tofu and sumedang fried tofu Mr. Osmandri agroindustry, (2) the totalproduction costs and income of sumedang raw tofu and sumedang fried tofu Mr.Osmandri agroindustry, (3) efficiency and the value added of sumedang raw tofuand sumedang fried tofu Mr. Osmandri agroindustry. The research result shows that(1) the profit of this agroindustry is Rp.27.317.339 in a month, (2) R/C Ratio value ofsumedang raw tofu is 1.46 and sumedang fried tofu is 1.29, the Break Event Pointvalue is obtained when producing 50.439 pcs sumedang raw tofu and selled 13.123pcs sumedang fried tofu, (3) The value added of sumedang raw tofu is Rp.7765/kgwith value added ratio 33,4% and the value added sumedang fried tofu isRp.115,67/pcs with value added ratio 17,4%.